Dynamics of the wood harvesting industry in the context of the circular economy - Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2025)
The problems of the forest industry complex in the context of a circular economy are substantiated, which can be described by the following points: loss of resources at the logging site, residues in processing processes, environmental pollution, inappropriate logging, which can lead to loss of biodiversity, market instability. The dynamics of the area of the forest fund of Ukraine in thousand hectares for the forty-two-year period from 1983 to 2025 are described, which, according to the State Agency of Forest Resources of Ukraine, is 10.4 million hectares. The dynamics of changes in wood reserves in the forests of Ukraine, million m3 for the thirty-seven-year period from 1988 to 2025, which as of 2025 is 2.3 billion m3, are presented. The dynamics of the area of forest regeneration in Ukraine, hectares for the eight-year period from 2019 to 2024 is described, which as of 2025 is 35.2 thousand hectares. The dynamics of wood harvesting in Ukraine, thousand m3 for the six-year period from 2019 to 2025 with growth and decline indices: 2019/2020 – 85.42%; 2020/2021 – 99.01%; 2021/2022 – 90.28%; 2022/2023 – 98.49%; 2023/2024 – 94.98% are analyzed. The dynamics of harvesting by tree species in Ukraine, thousand m3 are determined. m3, the analysis of which shows that coniferous timber accounts for 55.0-68.0%, and hardwoods are much less - in the range of 25.0-33.0% of all harvested wood. It was established that with wood harvesting in 2024 in the amount of 14905.8 thousand m3, as the lowest indicator for the analyzed period, the analysis of the dynamics of wood harvesting indicators in the context of a circular economy required the study of several key aspects, in particular the sustainability of wood harvesting of liquid wood and the processing of wood residues from all processes. Comprehensive ways of solving the problems of the forest industry complex are described and proposed, which include: creating a closed cycle of resource use; development of processing technologies, introduction of energy-efficient technologies for wood production and processing; continued implementation of forest use within the framework of sustainable development; stimulating the use of secondary raw materials; implementing circular business models; solving problems related to the involvement of used wood in production processes.